2012
DOI: 10.1007/s00280-012-1873-3
|View full text |Cite
|
Sign up to set email alerts
|

RY10-4, a novel anti-tumor compound, exhibited its anti-angiogenesis activity by down-regulation of the HIF-1α and inhibition phosphorylation of AKT and mTOR

Abstract: The structure of 4-hydroxy-2,5-cyclohexadien-1-one should be the effective pharmacophore of RY10-4. RY10-4 got fine performance in anti-tumor and anti-angiogenesis assay, and thus, the quinol compound will be the new hot-spot for further anti-tumor agency development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…This is also in line with previous studies that revealed increased levels of ROS in prostate and breast cancer cells after treatment with 1 or 2 [9,26]. Moreover, RY10-4, another synthetic protoflavone analog, was reported to down-regulate HIF-1α expression in breast cancer cell lines [29].…”
Section: Discussionsupporting
confidence: 84%
“…This is also in line with previous studies that revealed increased levels of ROS in prostate and breast cancer cells after treatment with 1 or 2 [9,26]. Moreover, RY10-4, another synthetic protoflavone analog, was reported to down-regulate HIF-1α expression in breast cancer cell lines [29].…”
Section: Discussionsupporting
confidence: 84%
“…In our laboratory, RY10-4 was designed and synthesized as a protoapigenone analog, as an attempt to develop a novel anti-tumor compound. According to some previously researches and reports [ 12 , 13 ], RY10-4 had potent anti-tumor activities against human breast cancer cells. In another report, RY10-4 could induce autophagic cell death in MCF-7 cells while protoapigenone could not [ 6 ].…”
Section: Discussionmentioning
confidence: 99%